Second sight : the visionary imagination in late Victorian literature - Maxwell, Catherine, 1962- (Manchester University Press ; Distributed in the USA exclusively by Palgrave Macmillan, 2009)
An innovative reassessment of late Victorian literature in its relation to visionary Romanticism. It examines the subject in relation to a range of writers of the period, including Pater Rossetti, Hardy and Vernon Lee.